Pengaruh Kepemimpinan dan Manajemen Kepala Sekolah Terhadap Kepuasan Kerja Guru di Sekolah Naungan Yayasan Cendekia dan Yayasan As-Salam Ambon - Sujana, Ujang; Ratumanan, T. G.; Rumfot, Sumarni (LP. Ma'arif Janggan Magetan, 2024)
This study aims to explore the influence of principal leadership and management on teacher job satisfaction in schools under the auspices of the Yayasan Cendekia Maluku and Yayasan As-Salam Ambon. This study is a quantitative study with an ex post facto design, involving 111 respondents as samples. The data analysis technique used is multiple regression analysis. The results of the study indicate that principal leadership has a positive and significant influence on teacher job satisfaction. Likewise, principal management also has a significant influence on teacher job satisfaction. In addition, principal leadership and management simultaneously have a significant influence on teacher job satisfaction. The conclusion of this study is that the better the principal leadership and management, the higher the teacher job satisfaction, and vice versa.